Exploring the Leidenfrost Effect for the Deposition of High‐Quality In2O3 Layers via Spray Pyrolysis at Low Temperatures and Their Application in High Electron Mobility Transistors. (6th April 2017) - Isakov, Ivan; Faber, Hendrik; Grell, Max; Wyatt‐Moon, Gwenhivir; Pliatsikas, Nikos; Kehagias, Thomas; Dimitrakopulos, George P.; Patsalas, Panos P.; Li, Ruipeng; Anthopoulos, Thomas D.
Abstract : The growth mechanism of indium oxide (In2 O3 ) layers processed via spray pyrolysis of an aqueous precursor solution in the temperature range of 100–300 °C and the impact on their electron transporting properties are studied. Analysis of the droplet impingement sites on the substrate's surface as a function of its temperature reveals that Leidenfrost effect dominated boiling plays a crucial role in the growth of smooth, continuous, and highly crystalline In2 O3 layers via a vapor phase‐like process. By careful optimization of the precursor formulation, deposition conditions, and choice of substrate, this effect is exploited and ultrathin and exceptionally smooth layers of In2 O3 are grown over large area substrates at temperatures as low as 252 °C. Thin‐film transistors (TFTs) fabricated using these optimized In2 O3 layers exhibit superior electron transport characteristics with the electron mobility reaching up to 40 cm 2 V −1 s −1, a value amongst the highest reported to date for solution‐processed In2 O3 TFTs. The present work contributes enormously to the basic understanding of spray pyrolysis and highlights its tremendous potential for large‐volume manufacturing of high‐performance metal oxide thin‐film transistor electronics. Abstract : The nucleation and growth of ultrathin indium oxide layers processed via ultrasonic spray pyrolysis in the temperature range of 100–300 °C, are studied. The Leidenfrost effect is shown to dominate material growth above 252 °C, leading to layers with exceptional crystallinity and uniformity. Transistors based on these layers exhibit remarkable electron mobility of 40 cm 2 V −1 s −1 .